2022
DOI: 10.3390/nu14153052
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Niacin Intake and Migraine among American Adults: National Health and Nutrition Examination Survey

Abstract: Migraine is related to brain energy deficiency. Niacin is a required coenzyme in mitochondrial energy metabolism. However, the relationship between dietary niacin and migraines remains uncertain. We aimed to evaluate the relationship between dietary niacin and migraine. This study used cross-sectional data from people over 20 years old who took part in the National Health and Nutrition Examination Survey between 1999 and 2004, collecting details on their severe headaches or migraines, dietary niacin intake, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 38 publications
1
35
0
2
Order By: Relevance
“…Other studies hold points that are similar to ours. Liu et al found that individuals who consumed more niacin had a lower incidence of Accepted Manuscript hypertension and diabetes [27]. Another study also proved that dietary niacin intake was negatively correlated with homeostasis model assessment of insulin resistance (HOMA-IR) (beta coefficient = -1.302, p = 0.009) and inflammatory markers in diabetes, adjusted for age, sex, BMI, and smoking [28].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies hold points that are similar to ours. Liu et al found that individuals who consumed more niacin had a lower incidence of Accepted Manuscript hypertension and diabetes [27]. Another study also proved that dietary niacin intake was negatively correlated with homeostasis model assessment of insulin resistance (HOMA-IR) (beta coefficient = -1.302, p = 0.009) and inflammatory markers in diabetes, adjusted for age, sex, BMI, and smoking [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this set of measurement guidelines was specifically designed for use in the current NHANES setting and was agreed upon by experts during regular workshops to evaluate NHANES data collection (Ahluwalia et al, 2016). The NHANES Dietary Interviewer Procedures Manual involves a complete overview of dietary survey methods (Liu et al, 2022). To make the results more convincing, we used the average of 2 days of dietary niacin intake in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of migraine was based on an affirmative answer to the question: “Have you had a severe headache or migraine in the past 3 months?” in the Miscellaneous Pain section of the questionnaire. It is reasonable to consider individuals with severe headache in NHANES having migraine, 18–20 and a review of statistics about the American Migraine Prevalence and Prevention Study and four national surveillance studies based on the US population including NHANES supported the view that most of the “severe” headaches were in fact migraine 21 . Mortality data were obtained by linkage of the cohort database to the Centers for Disease Control's National Death Index as of December 31, 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Family income was divided into three levels according to the poverty income ratio (PIR): low income (PIR ≤ 1.3), medium income (PIR = 1.3–3.5), and high income (PIR > 3.5) 26 . Smoking status was categorized as never, current, or former according to a previous study 19 . Participants were categorized according to alcohol drinking status as never (< 12 drinks in their lifetime), former (≥ 12 drinks in 1 year and did not drink last year, or did not drink last year but drank ≥ 12 drinks in their lifetime), or current drinkers (≥ 12 drinks in any 1 year and did drink last year).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation